PWE-022 Diagnosis and Management of Latent Tuberculosis and Its Treatment in IBD Patients Receiving Biologic Therapy. (17th August 2016) - Wolfson, P; Thi, AA; Bouri, S; Owen, L; Abbara, A; John, L; Davidson, RN; Hart, AL
Abstract : Introduction: Anti-TNF therapies for inflammatory bowel disease (IBD) can lead to a five fold increase of tuberculosis (TB) reactivation in patients with latent TB infection (LTBI). Current European Crohn's and Colits Organisation recommends LTBI screening with Interferon Gamma Release Assay (IGRA) according to local prevalence, national recommendations and preferred in BCG immunised individuals. In this study, we determine the proportion of LTBI in our cohort of IBD patients treated with biologics and any complications of treatment, particularly drug-induced liver injury (DILI). Methods: All patients with IBD who were treated with biologics between March 2007 and November 2015 were identified from the high cost funding database held at the Pharmacy of St Mark's Hospital. Case notes and electronic records were retrospectively reviewed to identify records of LTBI screening. The following were excluded from the analysis: those who were treated for active TB and those who did not receive treatment either for latent or active TB. Of note, at this site, in July 2013, an IGRA testing replaced the Mantoux on our screening algorithm. DILI was defined as deranged liver function tests with no other identifiable cause. Results: Seven hundred and thirty-two IBD patients were screened for TB prior to starting a biologic. 31 patients (4.2%) were identified as having LTBI and had prophylactic treatment for TB (19 with single agent isoniazid; 12 dual agent isoniazid and rifampicin). Of these 31 patients, 22 went on to have anti-TNF treatment with a median delay of 86 days (range = 7–336 days). Of the 31 that went on to have treatment for latent TB, 3% (n = 1) had side effects, dizziness which was not severe to be stopped the LTBI treatment and non had DILI. Conclusion: Rate of LTBI in this population receiving biologics for IBD was 4%; all identified patients were treated and none experienced significant side effects. The median time to starting biologics after screening was 86 days, which may represent a significant delay in starting biologics for the IBD patients; this could have detrimental effects to their IBD related morbidity. There remains the risk of false negative IGRA results in an immunosupressed patient and, as such, place of birth and likely previous exposure should be taken into account. Reference: 1 Rahier J, Moutschen M, Van Gompel A, Van Ranst M, Louis E, Segaert S, et al . Vaccinations in patients with immune-mediated inflammatory diseases. Rheumatology (Oxford) 2010;49 :1815–1827. Disclosure of Interest: None Declared